The Implementation Of The ATR/BPN E-Office Policy Implementation On Land Services At The Land Office Of Bandung Regency - Ade Irawan; Ade Silvina (Sean Institute, 2024)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) seeks to realize good governance through bureaucratic reform and the use of digital technology in public services, especially with the implementation of e-office. This study aims to analyze the effect of e-office policy implementation on land services at the Bandung Regency Land Office. The method used is an explanatory survey with respondents consisting of e-office administrators. The results showed that the implementation of the e-office policy was able to improve the efficiency of land services, although there were obstacles such as lack of staff training and ineffective communication. The conclusion of this study emphasizes the importance of leadership support, employee training, and the provision of adequate facilities to improve service quality. It is hoped that this research can serve as a reference for the development of better service policies and practices in the future.